Non-English major students’ perceptions and attitudes towards the use of the TOEIC Listening and Reading Test as a graduation requirement - Lê, Thị Nụ (2020)
The study aims mainly to investigate non-English major students’ perceptions of and attitudes towards the use of TOEIC Listening and Reading test scores to determine their graduation eligibility in some HE institutions. However, it is necessary to examine their perceptions of the English requirement policy for graduation in general first, and then their opinions about the appropriateness and effectiveness of the TOEIC as an exit test could reveal whether the test use is in line with the intended purposes of the policy. In order to achieve this aim, the following objectives were addressed in the study:- To identify how non-English major students perceive the English requirement policy for graduation- To investigate the opinions of the students who take the TOEIC Listening and Reading test for graduation about the appropriateness and effectiveness of this exit requirement.With these objectives in mind, the researcher conducted the study to answer these research questions:1. What are non-English major students’ perceptions of the English requirement policy for graduation?2. What are their perceptions of the appropriateness and effectiveness of the TOEIC as an exit test?